UPAYA PENINGKATAN KUALITAS DAN EFISIENSI PROSES PRODUKSI MEKANIS KURSI KANTOR DENGAN METODE LEAN SIX SIGMA DI PT. NUSAMULTI CENTRALESTARI - Lestari, Anggi; Hasanah, Ina Siti (Universitas Gunadarma, 2024)
The office chair mechanism is a tool used to adjust the height, backrest tilt, and armrest position of an office chair. PT. Nusamulti Centralestari faces issues of waste, low efficiency, and high defect rates. This research aims to identify types of defects and priority waste, calculate the sigma value, propose quality improvement suggestions, and evaluate the results using the DMAIC lean six sigma method. The research results indicate three priority types of defects: bubble painting (47.95%), slag welding (18.12%), and lumpy printing (14.03%). The types of waste include defects (average score of 4.4), inventory (average score of 4.2), and overprocessing (average score of 4.0). The sigma level before quality improvement was 3.3701 with Defect per Million Opportunities (DPMO) of 30,731.2696, and the production process efficiency was 72.55%. Proposed improvements for the bubbling paint defect include doing briefings and toolbox meetings regularly, enhancing process supervision, scheduling regular equipment maintenance, storing paint in a clean area, and scheduling room cleaning. Proposed improvements for slag welding and lumpy printing defects include doing briefings and toolbox meetings regularly, enhancing process supervision, and scheduling regular machine maintenance. Inventory waste is addressed by improving supervision and quality control and revising the SOP with simpler language. Over-processing waste is addressed by improving quality control and eliminating non-value-added (NVA) activities. After implementing lean Six Sigma, the sigma level increased to 3.5060 with a DPMO of 22427.4406, and the process efficiency increased to 74.09%.